Sales comparison approach, multiple regression analysis and the implicit prices of housing. Issue 3 (3rd July 2019) - Lisi, Gaetano
ABSTRACT: By using two of the main evaluation methods, namely the sales comparison approach and the multiple regression analysis, this paper points out the key role of implicit prices of housing characteristics in real estate appraisal. Firstly, this paper confirms the close link existing between the sales comparison approach and the multiple regression analysis. Furthermore, unlike examples in the related literature, this paper highlights the difference between marginal and implicit prices of housing characteristics. Although the related literature expresses awareness of the methodology for calculating marginal and implicit prices, there appears to be less awareness that implicit prices can: 1) lead to an estimate of the house price that is different from the regression model-predicted price; 2) replace the crucial and non-trivial phase of adjustment and reconciliation that characterises the main appraisal method, namely, the popular Sales Comparison Approach. Finally, an empirical analysis provides evidence of the key role of implicit prices in estimating house value.